Global environment outlook 3 : past, present and future perspectives (Earthscan Pub. LondonGB, 2002)
Presents a global overview. Directs a spotlight onto two or three key issues that are considered paramount in each of the seven arenas under each of eight environmental themes in turn: land, forests, biodiversity, freshwater, coastal and marine areas, atmosphere, urban areas and disasters. Highlights the evolution of environmental policy responses that society has (or sometimes has not) put in place to ensure environmental security and sustainability.
Keywords: ENVIRONMENT